Qatari foreign policy and the Arab Spring: From mediation to intervention - ElEtreby, Basma Mahmoud (AUC Knowledge Fountain, 2014)
This thesis examines the controversial role that Qatar has been playing in the Arab Spring, specifically from 2011 to 2013. Evidently, Qatari foreign policy will be assessed to comprehend the power this small state has been gaining in Middle East politics in a region plagued by never ending manifestations of power struggles and turbulent developments. The case studies of Egypt, Libya and Syria in which Qatari foreign policy involvement deployed the same rationale will be investigated to examine the increasing involvement of Qatar in Middle East politics. It concludes that the foreign policy of Qatar was both opportunistic and pro-Islamist and cannot be sustained as a distinctive foreign policy in the Middle East.